2022
DOI: 10.29219/fnr.v66.8226
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid ameliorates hepatic steatosis by modulating intestinal permeability and gut microbiota in ob/ob mice

Abstract: Background: Conjugated linoleic acid (CLA) is an effective supplement for reducing fat mass, but its effect on hepatic steatosis remains controversial. Objective: This study aims to evaluate the effect of CLA on liver fat accumulation, inflammation, gut microbiome, and intestinal barrier integrity. Design: Wild-type (WT) mice and ob/ob (OB) mice were randomly divided into four groups according to the treatment with/without 1% CLA: WT, WT mice treated with CLA (WT-CLA), OB, and OB mice treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…This study analyzed the gut microbiota of 204 twins from 129 families at three age stages and demonstrated that five gut microbiota, genera Akkermansia, Parabacteroides, Clostridium innocuum group, Roseburia , and Anaerostipes , were correlated with BMI_Z. As short-chain fatty acid producers, Akkermansia, Roseburia , and Anaerostipes were previously reported to be associated with obesity in animal models and adults ( Pinart et al, 2021 ; Gao et al, 2022 ; Pai et al, 2022 ; Xu et al, 2022 ; Zou et al, 2022 ). There were only two studies that reported a positive association between Akkermansia and BMI_Z in early childhood in singleton children, which was consistent with our findings ( Houtman et al, 2022 ; Reyna et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…This study analyzed the gut microbiota of 204 twins from 129 families at three age stages and demonstrated that five gut microbiota, genera Akkermansia, Parabacteroides, Clostridium innocuum group, Roseburia , and Anaerostipes , were correlated with BMI_Z. As short-chain fatty acid producers, Akkermansia, Roseburia , and Anaerostipes were previously reported to be associated with obesity in animal models and adults ( Pinart et al, 2021 ; Gao et al, 2022 ; Pai et al, 2022 ; Xu et al, 2022 ; Zou et al, 2022 ). There were only two studies that reported a positive association between Akkermansia and BMI_Z in early childhood in singleton children, which was consistent with our findings ( Houtman et al, 2022 ; Reyna et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…The Anaerovoraceae family has been associated with diabetic retinopathy. 81 The Tyzzerella genus has not been characterized per se but is often associated, together with other genera, with inflammation, [82][83][84] poor lifestyles 83,85 and diseases such as type 2 diabetes, 86 cardiovascular disease risk profile, 87 non-alcoholic fatty liver disease 88 and colorectal adenoma. 89 Thus, exposure to Mesosilver™ or AgC can deplete important beneficial bacterial taxa of the gut microbiota and increase the abundance of detrimental ones, although further characterization of identified genera is required.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al ( 60 ) also found that enrichment of several members of Alistipes genus seriously impaired gut barrier function. Additionally, according to Gao et al ( 61 ), the enrichment of the proinflammatory bacteria of the Alistipes genus might cause hepatic inflammation by managing mRNA expression of intestinal tight junctions proteins such as ZO-1, occludin that would then increase intestinal permeability. One of the specific microorganisms in the HFD group and a role in the serum rise of TC and TG were said to be the Turicibacter genus ( 62 ).…”
Section: Discussionmentioning
confidence: 99%